2013
DOI: 10.1111/jvim.12192
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Spontaneous Canine Hyperadrenocorticism: 2012 ACVIM Consensus Statement (Small Animal)

Abstract: Consensus Statements of the American College of Veterinary Internal Medicine (ACVIM) provide the veterinary community with up-to-date information on the pathophysiology, diagnosis, and treatment of clinically important animal diseases. The ACVIM Board of Regents oversees selection of relevant topics, identification of panel members with the expertise to draft the statements, and other aspects of assuring the integrity of the process. The statements are derived from evidence-based medicine whenever possible and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
346
4
69

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(428 citation statements)
references
References 102 publications
(153 reference statements)
9
346
4
69
Order By: Relevance
“…This finding was fairly surprising, as one would expect that cases with only mild clinical signs would have a lower degree of cortisol hypersecretion and a less decreased hypothalamic-pituitary-adrenal axis sensitivity than cases with more severe clinical signs (Behrend et al, 2013). On the one hand, the lack of correlation could be due to the subjectivity of the owner questionnaires.…”
Section: Discussionmentioning
confidence: 52%
“…This finding was fairly surprising, as one would expect that cases with only mild clinical signs would have a lower degree of cortisol hypersecretion and a less decreased hypothalamic-pituitary-adrenal axis sensitivity than cases with more severe clinical signs (Behrend et al, 2013). On the one hand, the lack of correlation could be due to the subjectivity of the owner questionnaires.…”
Section: Discussionmentioning
confidence: 52%
“…The intermediate IoI value of 1.1 for the ACTH stimulation test indicates that the ACTH stimulation test is suitable for use with population‐based reference intervals. However, the intermediate value of the IoI also reflects the reported uncertainty in the diagnosis of HC2 as exemplified below.…”
Section: Discussionmentioning
confidence: 94%
“…Veterinarians base the diagnosis of HC on supportive clinical signs, clinicopathologic changes, and specialized endocrine tests 2. A recent consensus statement from the American College of Veterinary Internal Medicine indicated that the diagnosis of HC depends on the demonstration of either increased cortisol production or decreased sensitivity of the hypothalamic‐pituitary‐adrenal axis to negative glucocorticoid feedback 2. The adrenocorticotropic hormone (ACTH) stimulation test is one of the specialized endocrine screening tests for HC that works by assessment of the adrenocortical reserve 2.…”
mentioning
confidence: 99%
“…Endogenous ACTH levels tend to be normal to elevated in cases of ACTHdependent hypercortisolism and are generally low or undetectable in dogs with adrenal tumors or iatrogenic hyperadrenocorticism (SCHIMMER;PARKER, 2007;BRÖMEL et al, 2013). The reference values vary depending on the technique used; thus, they vary between the levels established by each laboratory (BEHREND et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous ACTH concentration test is also recommended to differentiate the origin of hypercortisolemia, as it may be (adrenocorticotropic) primary or (pituitary) ACTH-dependent (NELSON, 2010;BEHREND et al, 2013). Its measurement is a good indication source when hypercortisolism diagnosis has already been established.…”
Section: Introductionmentioning
confidence: 99%